Gratitude and Adaptive Coping Among Chinese Singaporeans During the Beginning of the COVID-19 Pandemic - Tong, Eddie M. W.; Oh, Vincent Y. S. (Frontiers in Psychiatry, 2021)
We report results of a cross-sectional survey conducted during March-April 2020 which marked the start and escalation of the COVID-19 crisis in Singapore. Our purpose was to examine whether reported feelings of gratitude among Chinese Singaporeans (N = 371; 124 males, 247 females; Mage = 22.54, SDage = 3.63, age range: 18-53 years) could be linked to adaptive responses to the pandemic. The results revealed that gratitude was associated with stronger endorsement of virus-prevention measures (β = .25, p = .001) that are necessary for protecting the physical health of oneself and others but disruptive to daily lives. Gratitude was also positively related to the tendency to perceive meaningful benefits in the crisis (β = .25, p = .002). The magnitude of these relationships were in the moderate range and remained robust when controlling for other protective psychological factors (resilience and optimism), emotions, and key demographic variables. Among the emotions measured, gratitude was also reported the most strongly. The findings support theoretical models that gratitude facilitates prosocial inclinations and openness to different ways to support the well-being of others and suggest that in a collectivistic culture, gratitude could be a key resource enabling adaptation to a crisis.